Harnessing Organizational Creativity for Competitive Advantage: Management of Challenges - Khurana, Vijay Kumar; Sharma , C. S.; Gupta, Amit (Gyan Management Journal, 2014)
In today’s global marketplace, characterized by the increasing pace of competition, the increasing & changing demands of customers, and the explosion of knowledge and technology, all entities need creative ’out-of-the-box’ thinkers and approaches. Successfully navigating in this increasingly complex world requires creativity. Creativity can contribute significantly towards national growth by finding newer ways of solving macroeconomic and social problems, and by finding better ways of macroeconomic and social management. Creativity can also play a significant role in the growth and long-term survival of an organization. Creative thinking plays an enabling role in innovation. It is not possible to conceive innovation without creative ideas, as these are the starting point. This study has been undertaken from organizational perspective by conducting extensive literature review. The paper emphasizes the relevance of creativity for organizational survival and growth. The study explores the problems which crop up while harnessing the creative potential of employees. The paper suggests a framework for overcoming bottlenecks and stimulating creativity for attaining organizational competitive advantage. The paper proposes MEET model for harnessing orga11izational creativity.